2018
DOI: 10.17508/cjfst.2018.10.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical preservatives on quality attributes of orange juice

Abstract: Indexing p. 1  Editorial Bord p. 1  Guide for Authors p. 3  Manuscript preparation p. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…Thus, pasteurized wood apple beverage samples treated with a combination of 50 ppm and 100 ppm of preservatives were safe to drink for up to 50 days. The results of microbial evaluation found in this study is in accordance with the reports of Sasikumar [2] and Chowdhury et al [31] and are in agreement with the reports of Akinola et al [24], Ayub et al [25], Bhardwaj and Mukherjee [36], Khare et al [42], Dhaka et al [44] and Chatterjee et al [47].…”
Section: Changes In Microbial Loadsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, pasteurized wood apple beverage samples treated with a combination of 50 ppm and 100 ppm of preservatives were safe to drink for up to 50 days. The results of microbial evaluation found in this study is in accordance with the reports of Sasikumar [2] and Chowdhury et al [31] and are in agreement with the reports of Akinola et al [24], Ayub et al [25], Bhardwaj and Mukherjee [36], Khare et al [42], Dhaka et al [44] and Chatterjee et al [47].…”
Section: Changes In Microbial Loadsupporting
confidence: 93%
“…It was also revealed that the use of preservatives in wood apple beverage did not have a negative influence in the opinion of consumers. This finding is supported by the reports of Akinola et al and Sasikumar who reported that fruit beverages preserved using chemical preservatives can be acceptable to consumers [24].…”
Section: Changes In Sensory Attributessupporting
confidence: 75%
See 1 more Smart Citation
“…The results obtained in this study for the soluble solids are also similar to those reported by Akinola et al (2018), when they evaluated the chemical, microbiological and sensory characteristics of orange juice (C. × sinensis) samples chemically preserved in Akure (Nigeria), obtaining 9.40 ºBrix for the control sample (without preservatives) on the first day of analysis.…”
Section: Physicochemical Characterizationsupporting
confidence: 88%